Tube skin temperature prediction of catalytic reforming unit (CRU) heaters - S., Yusup; N.D., Vinh; N., Mellon; A., Hassan (2007)
The maximum duty of reformer heaters is governed by the occurance of maximum tube skin temperature of the heaters. The value of maximum tube skin temperatures of the heaters must not exceed theirs' maximum allowable design temperature. The paper highlights the simulation of the tube skin temperatures of CRU heaters and temperature distribution across the heater tubes. The simulated results are important in order to access the heaters performance and prediction of the coke formation in tubes. The simulated results are verified using Plant data. The simulation is done using finite element approach. A two dimensional model is developed with a front view and a cross-sectional view for each heater. The maximum percentage deviation of predicted tube skin temperature using Finite element approach was found to be 1.2%.